Effect of the infection with Schistosoma haematobium (Bilharz, 1952) on Bodyliver, spleen and kidney weight of laboratory Mus musculus mice - J. Razak, Sundus (University of Thi-Qar Journal of Science, 2012)
About 80 laboratory mice type BALB/c (40 male and 40 female) in age two months (40 animals)and three months (40 animals) before infection with Schistosoma haematobium were it are used in this study, 30 of these animals as a control group, and 50 of these were infected by cercaria of S. haematobium, the body wieght of infected and uninfected mice were measured after one, tow and three months of infection, and the weight of internal organs (liver, spleen and kidney) were measured in the same period as above. The results showed there was effect of infection on weight of body and other organs compared with uninfected mice. The body weight of infected mice was decreased compared with uninfected animals in all study period and in both genera that had the same age. Therefore, the liver, spleen and kidney weight were increased in infected animals especially in the second and third month of infection in. while the weight of liver and kidney of infected mice were decreased in the first month of infection compared withuninfected mice